Pariwisata Kreatif sebagai Strategi Revitalisasi Kawasan Perkotaan di Tangerang - Adrial Adrial; Sri Utami; Isaghoji Isaghoji (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Creative tourism emerges as an innovative approach to address the challenges of urbanization and the degradation of urban areas. Unlike mass tourism, which tends to be exploitative, creative tourism emphasizes the active involvement of visitors in activities rooted in local culture, arts, and creativity. This study aims to examine the role of creative tourism as a strategy for revitalizing urban areas in Tangerang City. Using a qualitative descriptive-analytical method, data were collected through field observations, interviews with stakeholders, and document analysis. The findings reveal that creative tourism fosters inclusive economic growth by increasing demand for local products, creating opportunities for small and medium enterprises, and generating multiplier effects in supporting sectors such as transportation, accommodation, and services. Moreover, creative tourism contributes to cultural preservation through art festivals, cultural workshops, and traditional performances that strengthen the city’s identity. The revitalization of public spaces and historic areas also enhances urban livability, making the city more attractive to both residents and visitors. The role of local government, multi-stakeholder collaboration, and digital technology support are crucial in strengthening the competitiveness of creative destinations. However, challenges such as cultural over-commercialization, limited creative human resources, and restricted access to financing remain. These issues require balanced, community-based policies to ensure sustainability. Overall, creative tourism proves to be a relevant strategy for sustainable urban development, integrating economic, social, cultural, and environmental dimensions.